2017
DOI: 10.1155/2017/8041962
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Neural Networks between Bimanual Antiphase and In-Phase Upper Limb Movements: A Preliminary Functional Magnetic Resonance Imaging Study

Abstract: Most daily movements require some degree of collaboration between the upper limbs. The neural mechanisms are bimanual-condition specific and therefore should be different between different activities. In this study, we aimed to explore intraregional activation and interregional connectivity during bimanual movement by functional magnetic resonance imaging (fMRI). Ten right-handed, normal subjects were recruited. The neural correlates of unimanual (right side) and bimanual (in-phase and antiphase) upper limb mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
(71 reference statements)
1
13
0
Order By: Relevance
“…Neural networks within and between hemispheres are necessary to coordinate motor functions not only for bilateral but also for unilateral movements. The neural network generating the coordination function between hemispheres was proposed to be the cingulate motor area and the cerebellum ( 55 ). The ipsilateral hemisphere involved in a motor task might contribute to the modulation, balance, or prohibition of the motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Neural networks within and between hemispheres are necessary to coordinate motor functions not only for bilateral but also for unilateral movements. The neural network generating the coordination function between hemispheres was proposed to be the cingulate motor area and the cerebellum ( 55 ). The ipsilateral hemisphere involved in a motor task might contribute to the modulation, balance, or prohibition of the motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Since Parallel movement requires more complex and carefully coordinated movements than Mirror movement, the contrast between the two is suitable for extracting higher-order motor cortical representations of complex control. Many previous imaging studies, including those using positron emission tomography (PET; Sadato et al, 1997 ), functional magnetic resonance imaging (fMRI; Haslinger et al, 2004 ; Wu et al, 2010 ; Lin et al, 2017 ), and functional near-infrared spectroscopy (fNIRS; Wilson et al, 2014 ), have shown that the supplementary motor area is more activated during Parallel than during Mirror movement tasks. In an fMRI study by Wu et al ( 2010 ) on PD, often highlighted in stuttering studies because of its shared features with stuttering (Alm, 2004 ), the control group showed higher activity in the supplementary motor area during Parallel movements compared with Mirror.…”
Section: Discussionmentioning
confidence: 99%
“…Another study utilized fMRI to compare the inter-regional connectivity and inter-regional activation between the bimanual in-phase and bimanual antiphase upper limb task in healthy individuals. Significant activation of the supplementary motor area, cerebellum, thalamus, and the cingulate motor area were observed during the bimanual antiphase task but not during in-phase movement [ 66 ]. The connectivity analysis also indicated stronger neural coupling during antiphase movement than during bilateral in phase and unimanual movement.…”
Section: Discussionmentioning
confidence: 99%